Sibilancias antes de los 3 años y antecedentes Familiares de asma como factores asociados en pacientes asmáticos mayores de 6 años que acuden a consulta de Neumología Pediátrica del Hospital San Bartolomé - Jugo Rebaza, Javier Nicolaz (2020)
Bronchial asthma is the most frequent chronic respiratory disease during childhood. Epidemiological studies in mainly Lima showed a prevalence ranging from 10 to 29%, considered a high prevalence worldwide. Frequent wheezing before 3 years of age and family history of asthma are considered fundamental on its prediction at 6 years old. The real reach in populations of high prevalence of asthma like ours is not known. Determine the association of the presence of frequent wheezing before 3 years of age and family history of asthma in asthmatic patients older than 6 years that attended the pediatric consultation. A prospective case-control study was carried out in “Hospital Nacional Docente Madre Niño San Bartolomé” where children over 6 years of age with a diagnosis of asthma (case) were selected and compared with a group of older children of 6 years without asthma (control) who attended pediatric consultation in the same Hospital between the months of June 2016 and February 2017. The parents or guardians of the children who match the inclusion criteria were given a questionnaire about respiratory symptoms at the age of 3 years or less and was determined the history of asthma in the family. It was excluded the children diagnosed with asthma without spirometry accord with international criterious for definitive diagnosis and controls if they had any suspicion of asthma symptoms at present. Children with respiratory diseases or pulmonary malformations from birth were excluded. From 229 children evaluated, 95 asthmatics children and 106 controls were selected, corresponding to 58.2% males. The average age was 8.35 years. It was found that asthmatic children had 12 times more association to frequent wheezing before 3 years than in controls with an OR 12.3 IC95% (4.04 – 49.8). The ones with only asthmatic father in the family is associated 7 times more to the presence of asthma at the age of 6 years or more compared to those who do not have a father with asthma with an OR 7.08 IC95% (0.828 – 328.5) with p=0.0436. Asthmatic patients had 19 times more wheezing in the past than controls with an OR 19.34 95% CI (5.71 – 100.51) with a highly significant p, this being present in 97% of asthmatics. CONCLUSIONS: Being a frequent and precocious sibilant child before 3 years old is a factor associated with the presence of asthma at the age of 6 years and over. Asthmatic children at the age of 6 are more associated with having an asthmatic father than with another family member with asthma.